Fermented food consumption in wild nonhuman primates and its ecological drivers - Amato, Katherine R. (2021)
Objectives: Although fermented food use is ubiquitous in humans, the ecological and evolutionary factors contributing to its emergence are unclear. Here we investigated the ecological contexts surrounding the consumption of fruits in the late stages of fermentation by wild primates to provide insight into its adaptive function. We hypothesized that climate, socioecological traits, and habitat patch size would influence the occurrence of this behavior due to effects on the environmental prevalence of late-stage fermented foods, the ability of primates to detect them, and potential nutritional benefits. Materials and methods: We compiled data from field studies lasting at least 9 months to describe the contexts in which primates were observed consuming fruits in the late stages of fermentation. Using generalized linear mixed-effects models, we assessed the effects of 18 predictor variables on the occurrence of fermented food use in primates. Results: Late-stage fermented foods were consumed by a wide taxonomic breadth of primates. However, they generally made up 0.01%–3% of the annual diet and were limited to a subset of fruit species, many of which are reported to have mechanical and chemical defenses against herbivores when not fermented. Additionally, latestage fermented food consumption was best predicted by climate and habitat patch size. It was more likely to occur in larger habitat patches with lower annual mean rainfall and higher annual mean maximum temperatures. Discussion: We posit that primates capitalize on the natural fermentation of some fruits as part of a nutritional strategy to maximize periods of fruit exploitation and/or access a wider range of plant species. We speculate that these factors contributed to the evolutionary emergence of the human propensity for fermented foods.